Study of Methanol Concentration and Refining Temperature on the Characteristics of Methyl Ester Sulfonate from Waste Cooking Oil - Hanjani Putri; Neswati -Neswati; Lisa Rahayu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Waste cooking oil is often disposed of carelessly, causing environmental pollution. Waste cooking oil still contains high levels of triglycerides, so it can be used in making surfactants. One environmentally friendly surfactant that can be derived from waste cooking oil is methyl ester sulfonate (MES). MES produced from the sulfonation process still contains di-salt. Di-salt can be reduced through a purification process. This research aimed to obtain the best methanol concentration and purification temperature for the characteristics of waste cooking oil. This study used a complete randomized design (CRD) factorial. The study used methanol concentrations of 40 %, 45 %, and 50 %, with purification temperatures of 45 °C, 50 °C, and 55 °C. The best outcome was obtained at a methanol concentration of 50% and a purification temperature of 55 °C, with characteristics including density 0.8626 g/mL, viscosity 2.3739 mPs, acid number 1.04 mg KOH/g, saponification number 152.87 mg KOH/g, and emulsion stability of 100%.